Geometric barriers impacted rupture processes and stress releases of the 2023 Kahramanmaraş, Türkiye, earthquake doublet - Jiangcheng Zhou; Yueyi Xu; Yong Zhang; Wanpeng Feng; Tuncay Taymaz; Yun-Tai Chen; Chenyu Xu; Beibei Xu; Rongjiang Wang; Fuqiang Shi; Zhigang Shao; Qinghua Huang (Communications Earth & Environment)
Abstract The 2023 Türkiye earthquake doublet, which includes two M W > 7.5 events, was the most devastating earthquake sequence globally over the past decade. Here we investigate the fault segmentations, rupture processes, radiated energy and stress releases of the doublet. Our findings reveal that the first earthquake was overall a subshear event, with local supershear ruptures that may have been induced by geometric barriers, while the second event exhibited persistent supershear ruptures on its geometrically simple segments. The difference in radiation efficiency between the two events suggests that the first event may be an undershoot event and/or that the second event may be an overshoot event. We speculate that the geometric barriers of the first event hindered the stress release, leading to rupture of more small asperities and generation of high-frequency signals. In contrast, the simpler fault geometry of the second event facilitates a larger stress drop and a more complete stress release.